Budgetary participation in managerial performance: an analysis mediated by sharing and use of information - Guterres, Marta; Lavarda, Carlos Eduardo (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2026)
Purpose: This study analyzed the relationship between budgetary participation and managerial performance, investigating the roles of information sharing and use of managerial information as potential mediating variables. Methodology: A quantitative approach was adopted, based on administering online questionnaires to 102 managers of companies associated with the Chamber of Commerce and Industry of Timor-Leste (CCI-TL). Partial least squares structural equation modeling (PLS-SEM) was employed for data analysis. Results: Budgetary participation positively influences managerial performance and is significantly related to information sharing and use of managerial information. While the use of managerial information had a mediating effect, there is no empirical evidence supporting the mediating role of information sharing in the relationship between budgetary participation and performance. Contributions of the Study: This study demonstrates that budgetary participation enhances the use of managerial information, thereby contributing to better managerial performance. Therefore, organizations are encouraged to actively involve managers in the budgeting process and promote the strategic use of information. This research expands our understanding of the mechanisms linking budgetary participation to managerial performance, highlighting the importance of information as a critical resource for decision-making and organizational efficiency.